A Five-Year Epidemiological Study of Extra-Pulmonary Tuberculosis and Its Related Risk Factors in Iran - Fallah, Sahar; Nasehi, Mahshid; Etemadinezhad, Siavash; Fallah, Simin; Yazdani Charati, Jamshid (Tanaffus, 2022)
Tuberculosis is the most common worldwide cause of death from microbial diseases. Extra-pulmonary tuberculosis accounts for 20% to 25% of all cases. In this study, we used generalized estimation equations to investigate the trend of changes in extra-pulmonary tuberculosis incidence. The recorded data of all patients with extra-pulmonary tuberculosis from 2015 to 2019 in Iran's National Tuberculosis Registration Center were included. The trend of standardized incidence changes in provinces of Iran was calculated and reported linearly. Also, we identified the risk factors related to the extra-pulmonary tuberculosis incidence in five consecutive years using generalized estimating equations. We studied the data of 12,537 patients with extra-pulmonary tuberculosis, of whom 50.3% were female. The mean age of the subjects was 43.61±19.88 years. Around 15.4% of all patients had a history of contact with a tuberculosis patient, 43% had a history of hospital stay, and 2.6% had a human immunodeficiency virus infection. Regarding disease types, 25% were lymphatic, 22% were pleural, and 14% were bone. Golestan province had the highest (average of 28.50 ± 8.65 cases), and Fars province had the lowest (average of 3.06 ± 0.75 cases) standardized incidences in these five years. Also, time trend ( < 0.001), employment rate ( = 0.037), and average annual rural income ( = 0.001) had a significant effect on reducing extra-pulmonary tuberculosis incidence. Extra-pulmonary tuberculosis has a decreasing trend in Iran. Still, Golestan, Sistan and Baluchestan, Hormozgan, and Khuzestan provinces have a higher incidence rate compared to the other provinces.